Pyridinone derivatives: specific human immunodeficiency virus type 1 reverse transcriptase inhibitors with antiviral activity. - Goldman, M E (1991)
Derivatives of pyridinones were found to inhibit human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) activity and prevent the spread of HIV-1 infection in cell culture without an appreciable effect on other retroviral or cellular polymerases. 3-[( (4,7-Dimethyl-1,3-benzoxazol-2-yl) methyl]amino ]-5-ethyl-6-methylpyridin-2(1H)-one (L-697,639) and 3-[[ (4,7-dichloro-1,3-benzoxazol-2-yl) methyl]amino]-5-ethyl-6-methylpyridin-2(1H)-one (L-697,661), two compounds within this series, had HIV-1 RT IC50 values in the range of 20-800 nM, depending upon the template-primer used. The most potent inhibition was obtained with rC.dG and dA.dT as template--primers. With rC.dG, reversible slow-binding non-competitive inhibition was observed. [3H]L-697,639 bound preferentially to enzyme-template-primer complexes. This binding was magnesium-dependent and saturable with a stoichiometry of 1 mol of [3H]L-697,639 per mol of RT heterodimer. Displacement of [3H]L-697,639 was seen with phosphonoformate. In human T-lymphoid-cell culture, L-697,639 and L-697,661 inhibited the spread of HIV-1 infection by at least 95% at concentrations of 12-200 nM. Synergism between 3'-azido-3'-deoxythymidine or dideoxyinosine and either of these compounds was also demonstrated in cell culture. Based upon their specificity for HIV-1 RT activity, template-primer dependence on potency and ability to displace [3H]L-697,639; a tetrahydroimidazo [4,5,1-jk] [1,4]-benzodiazepin-2(1H)-thione derivative R82150 and the dipyridodiazepinone BI-RG-587 appear to inhibit RT activity by the same mechanism as the pyridinones.